Antarctic ice sheet expansions in the Middle Miocene and Pliocene - Langebroek, Petra (Univ. Bremen, 2008)
This study focuses on the interactions between climate and ice sheets in order to obtain a better understanding of the processes involved. Two periods in the geological past are explored; the Middle Miocene and the mid-Pliocene. For both periods, foraminiferal oxygen-isotope records from deep-sea sediment cores as well as stratigraphical data, suggest a global sea-level lowering. The magnitude of these reductions in sea level indicate large-scale ice-sheet build-up. However, the origin of these events and even the geographic locations of the ice sheets, are still under discussion. The ice sheet-climate model developed in this study provides a tool to test some of the hypotheses brought forward to explain the ice-sheet expansion events. It describes the Antarctic ice sheet and is forced by a climate component based on energy and mass balances. Further more, the model computes the oxygen-isotopic composition of the ice-sheet, thereby providing the possibility to compare numerical results directly to deep-sea sediment records. Numerical experiments focus on the interactions between atmospheric CO2, temperature, ice volume (sea-level equivalent) and the isotopic composition of sea water. thesis